Protocol for Head StART: A hybrid type II cluster randomized controlled trial evaluating community ART delivery for people newly diagnosed with HIV in refugee settlements in Uganda - Robin E. Klabbers; Ambrose Mugyenyi; Rogers Nsubuga; Gloria Asaba; Zikama Faustin; Agnes Kiragga; Laura Drown; Andrew Mujugira; Melissa Mugambi; Monisha Sharma; Paul Drain; Nicholas A. Middleton; et al. (PLoS ONE, 2026)
Background Until recently, community-based antiretroviral therapy (ART) delivery was only available for people living with HIV on ART for ≥6 months with a suppressed viral load. However, early attrition from HIV care is common, particularly in refugee settlements where structural and psychosocial barriers to care are pronounced, and reducing barriers to life-saving ART sooner (e.g., at ART initiation) through community-based ART delivery may improve treatment outcomes. The Head StART study will evaluate the effectiveness, implementation, and health system costs of community ART delivery for individuals newly diagnosed with HIV in refugee settlements in Uganda. Methods In a cluster randomized trial, twelve health centers in five refugee settlements in Uganda were randomized (1:1) to intervention or standard of care (SoC), with stratification to balance site characteristics. Individuals testing positive for HIV are screened for study eligibility (inclusion criteria: diagnosed with HIV < 6 months, on ART ≤ 42 days, ≥ 18 years of age or emancipated minor or mature minor; exclusion criteria: pregnant/breastfeeding, medical reason for requiring facility-based care, concurrent trial participation) aiming to recruit up to 1,560 participants per arm (N = 3,120 total). Eligible individuals are enrolled and monitored longitudinally through abstraction of routinely collected data on HIV care outcomes. At intervention sites, participants are offered community ART delivery (Head StART intervention); at SoC sites, participants receive facility-based care. The primary outcome compares the proportion of participants virally suppressed 12 months post-ART initiation by arm in an intention-to-treat analysis. Qualitative interviews and direct observations will augment quantitative data to evaluate intervention implementation across sites. Micro-costing, time and motion observations, and costing interviews will assess intervention costs, which will inform a budget impact analysis. Discussion This trial will generate critical effectiveness, implementation, and budget impact data on community ART delivery for individuals newly diagnosed with HIV in refugee settlements needed to optimize HIV care for humanitarian populations. Trial registration ClinicalTrials.gov: NCT06126913. Registered 27 September 2023. https://clinicaltrials.gov/study/NCT06126913